The Effectiveness of Tax Incentives and Tax Revenue in Improving Village Tourism Infrastructure - Maria Sovia Dina; Herlambang Pudjo Santosa (Journal of Creative Power and Ambition (JCPA), 2026)
Tourism infrastructure development is a key factor in driving regional economic growth based on local potential. This study examines the influence of tax incentives and tax revenue on the quality of tourism infrastructure in Manggarai Regency. This study aims to analyze how regional fiscal dynamics influence infrastructure development in strategic tourism destinations. An associative quantitative approach was used in this study, with data collected from 110 respondents representing tourism service businesses and local government agencies. Multiple linear regression analysis was applied to test the relationship between variables. The results show that tax incentives have a positive and significant effect on the quality of tourism infrastructure. Tax revenue also shows a more dominant influence on infrastructure improvement. Simultaneous testing confirms that both variables jointly influence the quality of tourism infrastructure, with a coefficient of determination of 64.2 percent. This finding indicates that strengthening the synergy between tax incentive policies and effective tax revenue management plays a crucial role in supporting sustainable tourism infrastructure development in Manggarai Regency.